2021
DOI: 10.1097/ana.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

Brain Cancer Progression: A Retrospective Multicenter Comparison of Awake Craniotomy Versus General Anesthesia in High-grade Glioma Resection

Abstract: Background: High-grade gliomas impose substantial morbidity and mortality due to rapid cancer progression and recurrence. Factors such as surgery, chemotherapy and radiotherapy remain the cornerstones for treatment of brain cancer and brain cancer research. The role of anesthetics on glioma progression is largely unknown.Methods: This multicenter retrospective cohort study compared patients who underwent high-grade glioma resection with minimal sedation (awake craniotomy) and those who underwent craniotomy wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…However, this is a metaanalysis of observational/retrospective studies as the study authors have claimed. A retrospective multicentre study (891 patients) comparing AC (21%) and GA (79%) for HGG surgery found no difference in median PFS or median OS [7]. The recent multi-centre cohort study (GLIOMAP) by Gerritsen et al [17] on the effect of AC in glioblastoma in eloquent areas reported longer median PFS and median OS in AC versus asleep for cohort younger than 70 years (PFS: 9 The median PFS and median OS of 13 and 30 months, respectively in our study were also comparable to the numbers reported in literature [7,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is a metaanalysis of observational/retrospective studies as the study authors have claimed. A retrospective multicentre study (891 patients) comparing AC (21%) and GA (79%) for HGG surgery found no difference in median PFS or median OS [7]. The recent multi-centre cohort study (GLIOMAP) by Gerritsen et al [17] on the effect of AC in glioblastoma in eloquent areas reported longer median PFS and median OS in AC versus asleep for cohort younger than 70 years (PFS: 9 The median PFS and median OS of 13 and 30 months, respectively in our study were also comparable to the numbers reported in literature [7,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter retrospective study by Chowdhury et al, they compared the effect of awake craniotomy (AC) versus general anesthesia (GA) on progression-free survival (PFS) and overall survival (OS) in patients with high-grade gliomas undergoing surgical resection. 3 A total of 891 patients across five centers were included. The two groups were similar with respect to age, sex, location of the tumor, and preoperative Karnofsky Performance Status.…”
Section: Awake Craniotomy Versus General Anesthesia In Brain Cancer P...mentioning
confidence: 99%
“…Compared with awake surgery, surgery under general anesthesia is less time-consuming, with lower intraoperative risk ( 9 , 10 ). Cui et al.…”
Section: Clinical Studiesmentioning
confidence: 99%